Cortical output to fast and slow muscles of the ankle in the rhesus macaque - Hudson, Heather M.; Griffin, Darcy M.; Belhaj-Saïf, Abderraouf; Cheney, Paul D. (Frontiers in Neural Circuits, 2013)
The cortical control of fast and slow muscles of the ankle has been the subject of numerous reports yielding conflicting results. Although it is generally agreed that cortical stimulation yields short latency facilitation of fast muscles, the effects on the slow muscle, soleus, remain controversial. Some studies have shown predominant facilitation of soleus from the cortex while others have provided evidence of differential control in which soleus is predominantly inhibited from the cortex. The objective of this study was to investigate the cortical control of fast and slow muscles of the ankle using stimulus triggered averaging (StTA) of EMG activity, which is a sensitive method of detecting output effects on muscle activity. This method also has relatively high spatial resolution and can be applied in awake, behaving subjects. Two rhesus macaques were trained to perform a hindlimb push-pull task. Stimulus triggered averages (StTAs) of EMG activity (15, 30, and 60 μA at 15 Hz) were computed for four muscles of the ankle [tibialis anterior (TA), medial gastrocnemius (MG), lateral gastrocnemius (LG), and soleus] as the monkeys performed the task. Poststimulus facilitation (PStF) was observed in both the fast muscles (TA, MG, and LG) as well as the slow muscle (soleus) and was as common and as strong in soleus as in the fast muscles. However, while poststimulus suppression (PStS) was observed in all muscles, it was more common in the slow muscle compared to the fast muscles and was as common as facilitation at low stimulus intensities. Overall, our results demonstrate that cortical facilitation of soleus has an organization that is very similar to that of the fast ankle muscles. However, cortical inhibition is organized differently allowing for more prominent suppression of soleus motoneurons.